Breaking Down the Crystallinity: The Path for Advanced Lithium Batteries. Issue 5 (17th December 2015) - Zu, Chenxi; Dolocan, Andrei; Xiao, Penghao; Stauffer, Shannon; Henkelman, Graeme; Manthiram, Arumugam
Abstract : Lithium‐sulfur batteries offer high energy density, but their practical utility is plagued by the fast decay of lithium‐metal anode upon cycling. To date, a fundamental understanding of the degradation mechanisms of lithium‐metal anode is lacking. It is shown that (i) by employing a specifically designed electrolyte, the lithium‐metal anode degradation can be significantly reduced, resulting in a superior, high‐rate battery performance and (ii) by combining advanced, 3D chemical analysis with X‐ray diffraction, the properties of the lithium‐metal anode can be effectively monitored as a function of cycling, which is critical in understanding its degradation mechanisms. These findings suggest that the crystallinity of the impurity phases formed in the lithium‐metal anode via chemical reactions with the electrolyte is the dominant degradation factor. It is shown both experimentally and by computational modeling that by employing electrolyte additives containing metal ions that have lower reactivity with sulfur than lithium (e.g., copper, silver, and gold), the crystallinity of the impurity phases can be significantly reduced, resulting in a stable lithium‐metal anode. A pathway to develop a practical, affordable, environmentally compatible, rechargeable Li‐S battery system is offered, and insights to develop other high‐energy‐density battery systems based on the high‐capacity lithium‐metal anode are provided. Abstract : The crystallinity of impurities formed on lithium‐metal anodes via chemical reactions with the electrolyte is identified to be the dominating degradation factor of lithium‐metal anode in lithium‐sulfur batteries. The degradation can be suppressed with tailored electrolytes containing metal ions of lower reactivity with sulfur than lithium, which inhibit the passivation layer long‐range crystallinity and growth.